Zespół napięcia przedmiesiączkowego – mit czy rzeczywistość = Premenstrual syndrome – myth or reality - Pałucka, Klaudia; Łepecka-Klusek, Celina; Pilewska-Kozak, Anna; Pawłowska-Muc, Agnieszka Konstancja; Stadnicka, Grażyna (Journal of Education, Health and Sport, 2016)
Pałucka Klaudia, Łepecka-Klusek Celina, Pilewska-Kozak Anna B., Pawłowska-Muc Agnieszka K., Stadnicka Grażyna. Zespół napięcia przedmiesiączkowego – mit czy rzeczywistość = Premenstrual syndrome – myth or reality. Journal of Education, Health and Sport. 2016;6(6):478-490. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.56315 http://ojs.ukw.edu.pl/index.php/johs/article/view/3636 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.05.2016. Revised 25.05.2016. Accepted: 16.06.2016. Zespół napięcia przedmiesiączkowego – mit czy rzeczywistość Premenstrual syndrome – myth or reality Klaudia Pałucka ¹, Celina Łepecka-Klusek ², Anna B. Pilewska-Kozak ², Agnieszka K. Pawłowska-Muc ³, Grażyna Stadnicka 4 ¹ doktorantka w Katedrze i Klinice Ginekologii i Endokrynologii Ginekologicznej Wydział Nauk o Zdrowiu UM w Lublinie ² Katedra i Klinika Ginekologii i Endokrynologii Ginekologicznej Wydział Nauk o Zdrowiu UM w Lublinie ³ Powiatowe Centrum Medyczne w Grójcu Sp. z o. o 4 Zakład Podstaw Położnictwa Wydział Nauk o Zdrowiu UM w Lublinie mgr Klaudia Pałucka ¹, dr hab. n. med. Celina Łepecka-Klusek ², dr n. med. Anna B. Pilewska- Kozak ², mgr Agnieszka K. Pawłowska-Muc ³, dr n. med. Grażyna Stadnicka 4 Adres do korespondencji: Klaudia Pałucka Katedra i Klinika Ginekologii i Endokrynologii Ginekologicznej UM w Lublinie Al. Racławickie 23 20-049 Lublin, Poland tel./fax. 81-7183286 claudiapalucka@onet.pl Kierownik kliniki: prof. dr hab. n. med. L. Putowski Streszczenie Wprowadzenie. W drugiej fazie cyklu miesiączkowego u większości kobiet pojawiają się dość specyficzne objawy natury somatycznej i psychicznej, które uznawane są za fizjologię. U 20-40% z nich mogą jednak świadczyć o patologii. Cel pracy. Celem pracy było wyjaśnienie, czym jest zespół napięcia przedmiesiączkowego, jak go rozpoznać oraz na czym polega pomoc chorej kobiecie. Materiał i metoda. Przy użyciu haseł przedmiotowych przeszukano uniwersytecką bazę danych, PubMed i MEDLINE. Przeszukanie elektroniczne ograniczono do prac w języku polskim i angielskim, opublikowanych w latach 2005-2015. Wyłoniono ogółem 55 pozycji (głównie lekarskich), z czego wykorzystano 34 oraz jedną ze strony internetowej Amerykańskiego Towarzystwa Położników i Ginekologów. Opis zebranego materiału. Z przeglądu piśmiennictwa wynika, że zespół napięcia przedmiesiączkowego to nie mit, lecz realny problem osobisty i medyczny. Zaburza funkcjonowanie kobiet w życiu społecznym i zawodowym. Rozpoznanie wymaga minimum dwumiesięcznej obserwacji objawów oraz wykluczenia innych chorób. Modyfikacja stylu życia i ewentualne leczenie farmakologiczne poprawiają samopoczucie i jakość życia kobiet. Przegląd piśmiennictwa ukazał dużą rozbieżność stanowisk autorów w omawianych kwestiach oraz zasugerował kierunki dalszych dociekań. Słowa kluczowe: cykl miesiączkowy, zespół napięcia przedmiesiączkowego, dysforyczne zaburzenia przedmiesiączkowe. Summary Introduction. Specific symptoms of somatic and psychological nature appear in the second phase of the menstrual cycle of many women. These symptoms are considered to be physiological, however, 20-40 % of them may indicate pathology. Aim of the study. The aim of this study was to explain what the premenstrual syndrome is, how to recognize it and treat a sick woman. Material and methods. The university database, Pubmed and MEDLINE was searched, using subject headings. The electronic search was limited to the Polish and English papers, published in the period 2005-2015. A total of 55 items (mostly medical) was selected and 34 of them were used. One of the sources was the website of American College of Obstetricians and Gynecologist. Description of the collected material. A review of the literature shows that the premenstrual syndrome is not a myth, but a real personal and medical problem. It impairs the functioning of women in the social and professional lives. The diagnosis requires a minimum of two-month observation of symptoms and the exclusion of other diseases. The lifestyle modification and possible pharmacological treatment improve the well-being and quality of women’s lives. The reviewed literature revealed a large discrepancy in the views of the authors on these issues and suggested directions for the future research. Key words: menstrual cycle, premenstrual syndrome, premenstrual dysphoric disorder.